Validation of internal and external load metrics in NCAA D1 women's beach volleyball - Tometz, M. J.; Jevas, S. A.; Esposito, P. M.; Annaccone, A. R. (The Journal of Strength and Conditioning Research, 2022)
The purpose of this study was to determine the validity of internal and external load metrics in NCAA D1 women's beach volleyball. Subjects included 13 NCAA D1 women's beach volleyball players (age: 20.3 ± 1.4 years). A total of 578 data points were analyzed from 51 team training sessions, including practice, games, and sport-specific conditioning during the pre-season semester (15 weeks). Data points included Edward's training impulse (TRIMP) (228.0 ± 80.7 arbitrary units [AU]), session rating of perceived exertion (sRPE) Load (532.5 ± 232.8 [AU]), distance covered (DC) in meters (2,635.4 ± 884.3 [m]), and daily environmental condition variables {(temperature (76.5 ± 13.7 [°F]), relative humidity (72.5 ± 13.2 [%]), and wet-bulb globe temperature (52.9 ± 19.9 [°F])}. The subjects wore Polar Team Pro heart rate monitors with global positioning system during each session. Subjects completed an sRPE questionnaire after every session. Pearson product moment correlations yielded statistically significant relationships (p < 0.01) between TRIMP and sRPE Load (r = 0.81), TRIMP and DC (r = 0.78), and sRPE Load and DC (r = 0.82). A forward selection multiple regression yielded that sRPE Load could predict TRIMP with the equation: TRIMPTometz = 78.735 + (sRPE Load * 0.28) (p < 0.001). These findings support sRPE Load as a valid alternative to TRIMP when monitoring internal loads in NCAA D1 women's beach volleyball. Session rating of perceived exertion Load may be more practical and accessible for teams. Distance covered should be considered when periodizing and monitoring training loads because of its relationship with internal loads.